2016
DOI: 10.19044/esj.2016.v12n25p295
|View full text |Cite
|
Sign up to set email alerts
|

Capital Adequacy and Financial Performance of Banks in Nigeria: Empirical Evidence Based on the Fgls Estimator

Abstract: The study examines the degree of significance of the capital adequacy ratio in influencing the financial deeds of Nigerian banks by applying the feasible GLS estimator technique on the pooled panel model for the period of 2007 to 2015. Empirical evidence supports the overriding impact of capital adequacy in enhancing the financial deeds of Nigerian banks. Nevertheless, the impact of the estimated capital adequacy is below 30%. The policy stance of the empirics holds thus that depositor’s money in the banking s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 6 publications
(5 reference statements)
1
8
1
Order By: Relevance
“…These findings indicate that recapitalizations must be large enough to result in additional lending. In another study, Umoru & Osemwegie (2016), used the feasible GLS estimator approach on the pooled panel model to investigate the degree of relevance of the capital adequacy ratio in determining the financial behavior of Nigerian banks from 2007 to 2015. The dominating impact of capital adequacy in enhancing the financing demands of Nigerian banks was substantiated by empirical research.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…These findings indicate that recapitalizations must be large enough to result in additional lending. In another study, Umoru & Osemwegie (2016), used the feasible GLS estimator approach on the pooled panel model to investigate the degree of relevance of the capital adequacy ratio in determining the financial behavior of Nigerian banks from 2007 to 2015. The dominating impact of capital adequacy in enhancing the financing demands of Nigerian banks was substantiated by empirical research.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…As an illustration, Weber et al (2010) suggested the practice of an identical worldwide tax on forex dealings. These measures were not explicitly unusual until the 80s (Umoru & Osemwegie, 2016). But, due to the non-stop effort through establishments and the IMF for extra-liberalized emerging markets, the use of capital controls decreased until the Asian disaster (Milcheva et al, 2019).…”
Section: Liquidity Management and Financial Performancementioning
confidence: 99%
“…Furthermore, previous empirical studies show that studies involving board composition and bank performance as well as board size and bank performance are mainly investigated using quantitative approaches (Andres & Vallelado, 2008;Duru et al, 2015;Fanta et al, 2013;James & Joseph, 2015;Liu et al, 2015;Mehrotra, 2016;Pandya, 2011;Salim et al, 2016;Zhou et al, 2016). The regulatory monitoring mechanism is represented by the capital adequacy ratio attribute, which emphasizes financial regulation to enhance corporate governance of banks (Andres & Vallelado, 2008;Hwa-Jin, 2016;Onakoya et al, 2012;Umoru & Osemwegie, 2016). Quantitative approaches have been used in studies involving capital adequacy ratio and bank performance (James & Joseph, 2015;Praptiningsih, 2009;Umoru & Osemwegie, 2016).…”
Section: Empirical Reviewmentioning
confidence: 99%
“…The regulatory monitoring mechanism is represented by the capital adequacy ratio attribute, which emphasizes financial regulation to enhance corporate governance of banks (Andres & Vallelado, 2008;Hwa-Jin, 2016;Onakoya et al, 2012;Umoru & Osemwegie, 2016). Quantitative approaches have been used in studies involving capital adequacy ratio and bank performance (James & Joseph, 2015;Praptiningsih, 2009;Umoru & Osemwegie, 2016). A review of empirical research on the disclosure/transparency monitoring mechanism of corporate governance shows that the independent audit committee attribute is used to guide and monitor banks' performance (Fanta et al, 2013;Kamau et al, 2018).…”
Section: Empirical Reviewmentioning
confidence: 99%